Partnering a Three‐Coordinate Gallium Cation with a Hydroborate Counter‐Ion for the Catalytic Hydrosilylation of CO2. Issue 6 (28th December 2020) - Caise, Alexa; Hicks, Jamie; Ángeles Fuentes, M.; Goicoechea, Jose M.; Aldridge, Simon
Abstract: A novel β‐diketiminate stabilized gallium hydride, ( Dipp L)Ga(Ad)H (where ( Dipp L)=HC(MeCDippN)2 , Dipp=2, 6‐diisopropylphenyl and Ad=1‐adamantyl), has been synthesized and shown to undergo insertion of carbon dioxide into the Ga−H bond under mild conditions. In this case, treatment of the resulting κ 1 ‐formate complex with triethylsilane does not lead to regeneration of the hydride precursor. However, when combined with B(C6 F5 )3, ( Dipp L)Ga(Ad)H catalyses the reductive hydrosilylation of CO2 . Under stoichiometric conditions, the addition of one equivalent of B(C6 F5 )3 to ( Dipp L)Ga(Ad)H leads to the formation of a 3‐coordinate cationic gallane complex, partnered with a hydroborate anion, [( Dipp L)Ga(Ad)][HB(C6 F5 )3 ]. This complex rapidly hydrometallates carbon dioxide and catalyses the selective reduction of CO2 to the formaldehyde oxidation level at 60 °C in the presence of Et3 SiH (yielding H2 C(OSiEt3 )2 ). When catalysis is undertaken in the presence of excess B(C6 F5 )3, appreciable enhancement of activity is observed, with a corresponding reduction in selectivity: the product distribution includes H2 C(OSiEt3 )2, CH4 and O(SiEt3 )2 . While this system represents proof‐of‐concept in CO2 hydrosilylation by a gallium hydride system, the TOF values obtained are relatively modest (max. 10 h −1 ). This is attributed to the strength of binding of the formatoborate anion to the gallium centre in the catalytic intermediate ( Dipp L)Ga(Ad)OC(H)OB(C6 F5 )3 , and the correspondingly slow rate of the turnover‐limiting hydrosilylation step. In turn, this strength of binding can be related to the relatively high Lewis acidity measured for the [( Dipp L)Ga(Ad)] + cation (AN=69.8). Abstract : Selective : Addition of one equivalent of B(C6 F5 )3 to ( Dipp Nacnac)Ga(Ad)H leads to the formation of a 3‐coordinate cationic gallane, partnered with a hydroborate anion, [( Dipp Nacnac)Ga(Ad)][HB(C6 F5 )3 ], which catalyses the selective reduction of CO2 to the formaldehyde oxidation level, yielding H2 C(OSiEt3 )2 .